2021
DOI: 10.1182/bloodadvances.2020003093
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of NADPH oxidase blocks NETosis and reduces thrombosis in heparin-induced thrombocytopenia

Abstract: Heparin-induced thrombocytopenia (HIT) is associated with severe and potentially lethal thrombotic complications. NETosis was recently shown to be an important driver of thrombosis in HIT. We investigated the role of reactive oxygen species (ROS) and NADPH oxidase 2 (NOX2) and their contributions to thrombus development in HIT. We showed that neutrophil activation by HIT immune complexes induced ROS-dependent NETosis. Analysis of thrombi formed in a microfluidics system showed ROS production in both platelets … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 54 publications
0
20
0
Order By: Relevance
“…The requirement or dispensability of dinucleotide phosphate (NADPH) oxidase (NOX) activity, reactive oxygen species (ROS), and calcium influx on VITT IgG-induced NETosis requires further research. We have previously shown that PAD4, ROS and NOX2 play a crucial role in NETosis and thrombosis in HIT 10 . Due to the analogous nature of HIT and VITT, NET formation is likely dependent on both PAD4 and NADPH oxidase, as in HIT.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The requirement or dispensability of dinucleotide phosphate (NADPH) oxidase (NOX) activity, reactive oxygen species (ROS), and calcium influx on VITT IgG-induced NETosis requires further research. We have previously shown that PAD4, ROS and NOX2 play a crucial role in NETosis and thrombosis in HIT 10 . Due to the analogous nature of HIT and VITT, NET formation is likely dependent on both PAD4 and NADPH oxidase, as in HIT.…”
Section: Discussionmentioning
confidence: 93%
“…In HIT, we have previously shown that thrombosis is driven by NETosis 10 , 11 . Upon activation by pathogens, immune complexes and other stimuli, neutrophils release their granules and decondensed chromatin in the form of a DNA network, termed Neutrophil Extracellular Traps (NETs).…”
Section: Introductionmentioning
confidence: 99%
“…However, further research is necessary to understand the underlying principles in detail [ 162 ]. Studies already performed have shown that ROS mainly contribute to a proinflammatory response, which is associated with activation of platelets and subsequent trapping in the microcirculation leading to thrombocytopenia [ 163 , 164 ]. Nox2 activation is critically involved in platelet activation and thrombosis in response to oxidative stress [ 165 ].…”
Section: Methodsmentioning
confidence: 99%
“…The contact factor FXIIa, activated by polyphenols released from activated platelets, is an important component in clot formation [ 166 , 167 ], and TF promotes neutrophil extracellular trap (NET) formation, a process which is called NETosis [ 168 ], and disease progression [ 169 ]. NETosis is directly associated with ROS release, as shown in mice where NADPH oxidase inhibition blocked NETosis and improved thrombosis [ 163 ]. Complement activation, a characteristic event in infection, is involved in thrombosis and disseminated intravascular coagulation (DIC).…”
Section: Methodsmentioning
confidence: 99%
“…The assembled NOX complex generates ROS by transferring one electron from NADPH to the cytosol O 2 . NOX enzymes are widely distributed across different cells and tissues, while NOX2 is highly expressed in neutrophils and is rapidly activated to generate large quantities of ROS in response to external stressors (Leung et al, 2021).…”
mentioning
confidence: 99%